2016
DOI: 10.1007/s10750-016-3043-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and multi-annual patterns of colonisation and growth of sessile benthic fauna on artificial substrates in the brackish low-diversity system of the Baltic Sea

Abstract: Although benthic succession is well understood, the growth of assemblages does not follow the same progression across environmental variables and differs among coastal ecosystems. This study investigates the seasonal and multi-annual patterns of development of sessile invertebrate assemblages and the effects of environmental variables and substrate orientation (topsurface vs. undersurface) on this process. Perspex panels deployed on the seafloor horizontally were monitored seasonally from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In the present study, the total coverage in STP peaked by the end of summer and beginning of autumn, when temperature and chlorophyll a exhibited their highest values. In accordance with these results, Sokołowski et al (2017) based on a monitoring performed in the Baltic coast of Poland, argued that the increase of temperature and light availability during spring and summer promotes the reproduction and spawning of epibenthic species, explaining a higher recruitment in summer. Similar results were observed for the barnacle A. improvisus, the dominant species in this study, which massively recruits during summer in the South Western Baltic Sea (Thomsen et al 2010, Nasrolahi et al 2012.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present study, the total coverage in STP peaked by the end of summer and beginning of autumn, when temperature and chlorophyll a exhibited their highest values. In accordance with these results, Sokołowski et al (2017) based on a monitoring performed in the Baltic coast of Poland, argued that the increase of temperature and light availability during spring and summer promotes the reproduction and spawning of epibenthic species, explaining a higher recruitment in summer. Similar results were observed for the barnacle A. improvisus, the dominant species in this study, which massively recruits during summer in the South Western Baltic Sea (Thomsen et al 2010, Nasrolahi et al 2012.…”
Section: Discussionsupporting
confidence: 57%
“…The temporal variability observed in the coverage for the whole community was mostly driven by the recruitment patterns of barnacles and bryozoans (see Figs 3 and 5). Recent studies have shown that temporal changes in temperature, salinity, photoperiod and primary production influence the reproduction and recruitment of single species, and in consequence, the seasonal patterns observed in fouling communities (e.g., , Sokołowski et al 2017. In the present study, the total coverage in STP peaked by the end of summer and beginning of autumn, when temperature and chlorophyll a exhibited their highest values.…”
Section: Discussionsupporting
confidence: 52%
“…Regarding the density and local occurrence of these two non-native species, we considered their potential contribution to the meroplankton of our study area negligible. This assumption is supported by the lack of any recruitment event on artificial substrates in this area during 7 years of observations (Brzana & Janas, 2016;Sokołowski et al, 2017).…”
Section: Identification Of the Larvaementioning
confidence: 63%
“…In invaded systems, Bivalvia (31.28%) and Cirripedia (17.72%) were the most frequent taxa associated with false mussel clusters. These two groups are the commonest sessile invertebrates on the hard substrate of brackish areas around the world (Grzelak and Kuklinski 2010;Oganjan et al 2017;Sokołowski et al 2017). Our results presented a snapshot of the distribution and co-occurrence of Mytilopsis populations with several epibenthic taxa, but our data is not appropriate to indicate changes in the pattern of epibenthic communities related to false mussels' invasion.…”
mentioning
confidence: 58%